Theoretical foundations, condition and practice of development of payment systems in Ukraine - Volodymyr Chernomor (Cхід, 2017)
In modern conditions payment systems have an important role in the economy, as they must provide effective economic means of payments. Accordingly, the development of payment systems in Ukraine appears as a relevant theoretical and practical problem.